'You're 18 now, goodbye': the experiences of young people with attention deficit hyperactivity disorder of the transition from child to adult services. Issue 3 (3rd July 2018) - Newlove-Delgado, Tamsin; Ford, Tamsin J.; Stein, Ken; Garside, Ruth
ABSTRACT: The term 'transition' is used to refer to the process of moving from child to adult services. Among child and adolescent mental health services attenders, young people with Attention Deficit Hyperactivity Disorder (ADHD) are less likely to transition successfully, but there is a gap in understanding their views and why they might disengage from services. The aim of this study was to explore the experiences of transition of young people with ADHD in Southwest England using semi-structured interviews and thematic analysis. Seven young people aged 17–19 years participated. Four key themes were identified: professionals' roles and relationships with young people; the role of ADHD medication, uncertainties around transition and medication management, and identified needs and increasing independence. Although this study presents the experiences of a small number of people, their stories suggest that best practice around transition is not always being followed. There is consequently a need to better understand the facilitators and barriers to best practice implementation.